Carbon dynamics and environmental controls of a hilly tea plantation in Southeast China. Issue 17 (31st July 2019) - Pang, Jiaping; Li, Hengpeng; Tang, Xuguang; Geng, Jianwei
Abstract: Tea plantations are widely distributed and continuously expanding across subtropical China in recent years. However, carbon flux exchanges from tea plantation ecosystems are poorly understood at the ecosystem level. In this study, we use the eddy covariance technique to quantify the magnitude and temporal variations of the net ecosystem exchange (NEE) in tea plantation in Southeast China over four years (2014–2017). The result showed that the tea plantation was a net carbon sink, with an annual NEE that ranged from −182.40 to −301.51 g C/m 2, which was a much lower carbon sequestration potential than other ecosystems in subtropical China. Photosynthetic photon flux density (PPFD) explained the highest proportion of the variation in NEE and gross primary productivity (GPP) (for NEE: F = 389.89, p < .01; for GPP: F = 1, 018.04, p < .01), and air temperature (Ta ) explained the highest proportion of the variation in ecosystem respiration (RE) ( F = 13, 141.81, p < .01). The strong pruning activity in April not only reduced the carbon absorption capacity but also provided many plant residues for respiration, which switched the tea plantation to a carbon source from April to June. Suppression of NEE at higher air temperatures was due to the decrease in GPP more than the decrease in RE, which indicated that future global warming may transform this subtropical tea plantation from a carbon sink to carbon source. Abstract : Annual NEE of tea plantation ranged from −182.40 to −301.51 g C/m 2 . The variation of NEE and GPP was controlled by PPFD, and the variation of RE was controlled by daily Ta . The strong pruning activity in April switched the tea plantation to a carbon source from April to June. GPP decreased greatly than RE at higher temperature, indicating that GPP was more sensitivity to warming in this tea plantation.